2021
DOI: 10.1002/cbin.11750
|View full text |Cite
|
Sign up to set email alerts
|

TRIM7 suppresses cell invasion and migration through inhibiting HIF‐1α accumulation in clear cell renal cell carcinoma

Abstract: Clear cell renal cell carcinoma (ccRCC) is one frequent form of urologic malignancy characterized by deregulated hypoxia-inducible factor signaling, genetic and epigenetic alterations. Metastasis is the leading cause of mortality from ccRCC, and understanding the underlying mechanism of this event will provide better strategies for its management. Here, we identify tripartite motif containing 7 (TRIM7) as a tumor suppressor in ccRCC cells, which negatively regulates hypoxia-inducible factor 1α (HIF-1α) signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In renal cell carcinoma, multiple TRIM proteins had been reported to be associated with cancer development and prognosis. For instance, TRIM7 was identified as a tumor suppressor in ccRCC by decreasing the levels of Src protein via the ubiquitin-proteasome pathway, hence exerting a negative regulatory effect on HIF-1 signaling [ 34 ]. The expression of TRIM21 was significantly reduced in renal cell carcinoma, and this decreased expression was linked to unfavorable clinicopathological features and decreased overall survival in RCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…In renal cell carcinoma, multiple TRIM proteins had been reported to be associated with cancer development and prognosis. For instance, TRIM7 was identified as a tumor suppressor in ccRCC by decreasing the levels of Src protein via the ubiquitin-proteasome pathway, hence exerting a negative regulatory effect on HIF-1 signaling [ 34 ]. The expression of TRIM21 was significantly reduced in renal cell carcinoma, and this decreased expression was linked to unfavorable clinicopathological features and decreased overall survival in RCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…The higher the concentration of propofol is, the stronger the apoptosis-promoting ability of propofol is. In addition, activating the apoptosis pathway of tumor cells can induce the release of many inflammatory factors, which in turn activate the process of autophagy and promote the apoptosis of tumor cells (16). TGF-β1, IL-6 and TNF-α are all important inflammatory regulatory cytokines, among which TGF-β1 and TNF-α are endogenous cytokines, which can promote the release of proinflammatory factors by activating middle lymphocytes, macrophages, neutrophils, and other immune inflammatory cells, while IL-6 can induce acute inflammatory response by promoting the activation of lymphocytes in blood (17).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Zhou et al found that TRIM7 promoted osteosarcoma cell migration and invasion through ubiquitinating breast cancer metastasis suppressor 1 at the K184 site [ 30 ]. In contrast, other findings showed that TRIM7 could suppressed tumor growth in vivo and in vitro [ [31] , [32] , [33] ]. In the present study, we aim to decipher the role and mechanisms of TRIM7 in the progression of glioblastoma.…”
Section: Introductionmentioning
confidence: 90%